Histopathology of the liver of Mastacembelus armatus (Lecepede, 1800) due to trematode parasite, Allocreadium khami n.sp - P. R. Pardeshi (2018)
The trematode parasite, Allocreadium khami n. sp. cyst is found infected to the liver of freshwater fish, Mastacembelus armatus (Lecepede, 1800). Histopathological studies have been made to access the extent of damage caused by the parasite. The changes that have witnessed in the liver includes inflammation of liver, change of colour and formation of cysts. The histopathological changes include disarray in the arrangement of hepatochords, arrangement and rupture of hepatocytes. © 2012 Indian Society for Parasitology.